Peningkatan Hasil Belajar Matematika dan Respon Siswa Melalui Pembelajaran Kooperatif Tipe STAD dengan Metode Penemuan Terbimbing - Yuni Rhamayanti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2019)
This study was conducted on junior high school students with the aim to improve the learning outcomes of mathematics, student activities, and student responses through the application of the STAD type cooperative learning model with guided discovery method. This type of research is Classroom Action Research, ie research done by teachers in their own class with planned, systematic to improve the quality of classroom learning practice. The subjects of this study are students of class VII SMP Negeri Padangsidimpuan Lesson Year 2017-2018, selected is a class VII-2 with the number of students 31 people. While the object of this study is the application of the STAD type cooperative learning model with a guided discovery method to improve results and student learning activities that are not good math and need to be improved. The research instrument in this research will use test and non-test technique. The conclusion that can be drawn from this research is 1) the increase of mathematics learning outcomes through the application of STAD type cooperative learning model with guided discovery method of 0.65 with medium criteria, 2) Increased student learning activity through the application of STAD type cooperative learning model with guided discovery method equal to 0.46 with medium criterion, 3) also increase student response to STAD type cooperative learning with guided discovery method. The improvement of teachers' ability to manage the learning is 0.78 with high criteria.